1995
DOI: 10.1016/0022-3115(94)00443-9
|View full text |Cite
|
Sign up to set email alerts
|

Divertor heat and particle control experiments on the DIII-D tokamak

Abstract: This isa preprintof a paperto be presented at the EleventhInterna-tionalConference onPlasmaSurfaceInteractions inControlledFusion Devices,May23-27, 1994, Ibaraki-ken, Japan,andto be printedin the PROCEEDINGS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…5.2, have been successfully applied to study SOL and divertor plasma experiments, and in many cases are reasonably successful in describing the observed phenomena. The results are in satisfactory agreement with observations of divertor detachment [144]. In these models, it is seen that carbon impurities, sputtered physically and chemically from the graphite divertor strike-plates, radiate as part of an uncontrolled but self-regulating loop.…”
Section: Power Dispersal and Removalsupporting
confidence: 82%
“…5.2, have been successfully applied to study SOL and divertor plasma experiments, and in many cases are reasonably successful in describing the observed phenomena. The results are in satisfactory agreement with observations of divertor detachment [144]. In these models, it is seen that carbon impurities, sputtered physically and chemically from the graphite divertor strike-plates, radiate as part of an uncontrolled but self-regulating loop.…”
Section: Power Dispersal and Removalsupporting
confidence: 82%
“…The core density control experiments with active cryopumping are discussed in detail elsewhere [3]; briefly, these studies showed effective control of the core electron density. Efficient pumping, as expected, was obtained when the plasma separatrix was placed close to the pump entrance; the pumping rate decreased rapidly when the separatrix was moved away from the pump.…”
Section: Summary Ofrecent Experimental Results Usedtodesign Thediii-dmentioning
confidence: 99%
“…[2], for an overview of divertor results see Ref. [3], and a detailed overview of gas puffing results is presented in Ref. [4].…”
Section: Introductionmentioning
confidence: 99%
“…Besides these favorable pressure buildup measurements, tokamaks have added active pumps during the EDA. In ELMing H-mode it has proven possible to exhaust the fuel at a sufficient rate to lower the main plasma density a factor of 2 from the normal H-mode level to the L-mode level [30]. It appears a sound physics basis exists for the necessary fuel and helium exhaust in ITER.…”
Section: Particle Controlmentioning
confidence: 99%